Growth, mortality and yield per recruit of Johnius macrorhynus (Mohan) from Mumbai coast - Chakraborty, S K; Biradar, R S; Jaiswar, A K; Palaniswamy, R (Indian Journal of Fisheries, 2011)
Growth, mortality and yield per recruit of Johnius macrorhynus, one of the dominant species of lesser sciaenids is reported. Employing ELEFAN programme, the von Bertalanffyâ€™s growth parameters Lâˆž and K were estimated as 349 mm and 0.79/year. The total, natural and fishing mortalities were calculated as 3.86, 1.47 and 2.14 respectively. The exploitation ratio and rate were worked out as 0.62 and 0.61 respectively. The knife edge and selection ogive gave Emax of 0.78 and 0.62 respectively. Based on the yield-isopleth diagram, it appears that the stock of J. macrorhynus belongs to the category where fishery is well developed and large sized fish can be captured by increasing efforts. However, as it would be detrimental to the stock in the long run, it is better to carry out fishing at the present level or it can even be slightly reduced